Penggunaan Kunyit (Curcuma domestica Val.) dan Kandistatin® untuk Penanganan Penyakit ORF pada Kambing Saanen: Studi Kasus di BBPTU-HPT Baturraden: Use of Turmeric (Curcuma domestica Val.) and Kandistatin® to Treat ORF Disease in Saanen Goats: Case Study at BBPTU-HPT Baturraden - Wibowo, Sarwo Edy; Alfandi, Surya; Manin, Fahmida; Rahayu, Pudji; Insulistyowati, Anie; Darlis, Darlis; Maksudi, Maksudi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2024)
Background: ORF disease is also called Contagious Ecthyma (CE), Contagious Pustular Dermatitis (CPD), Sore Mouth which is caused by viruses from the genus Parapoxvirus which attacks goats and sheep. Orf disease is very easily transmitted to goats and sheep, and is zoonotic. Purpose: This study aims to determine the effectiveness of using turmeric and Kandistatin® for the treatment of ORF disease at BBPTU-HPT Baturaden. Methods: This section should include a concise description of the process by which you conducted your research. Results: Based on the results of the anamnesis, physical examination and clinical symptoms of Saanen goats in cage G at the Balai Besar Pembibitan Ternak Unggul dan Hijauan Pakan Ternak (BBPTU-HPT) Baturraden, there are 3 goats infected with ORF disease with eartag numbers 1861, 1985, and 1986. Saanen goats is + 4 months old. Saanen goats that had ORF infections were treated using grated turmeric mixed with vegetable oil which was applied to the goat's lips and given 1 ml of Kandistatin® twice a day for 7 days, showing the healing process on the third day and the seventh day. The examination results showed healing. Conclusion: The use of turmeric mixed with vegetable oil and the administration of Kandistatin® can be used to treat ORF infections.